Quality of life for people with psychiatric disabilities employed in extended employment programs in two Arab towns in Israel: an exploratory study - Badran, Leena; Rosenbaum, Stephen; Rimmerman, Arik (Frontiers in Psychiatry, 2023)
This study aims to examine the quality of life (QOL) for people with psychiatric disabilities who are engaged in extended employment programs (homogeneous versus heterogeneous) in the Arab-populated Triangle Area of Israel. The homogeneous program participants are exclusively Arab while the heterogeneous program includes both Arabs and Jews. Methods: Quantitative research study of 104 adults with psychiatric disabilities engaged in two communal extended employment programs. Participants completed demographic (age (years), gender, marital status (married, widowed/separated, married, single), religion (Muslim, Jewish, Christian), dichotomous nationality variable (Jewish/Arab), and years of education) and employment questionnaires (length of time in the employment program, number of working days/hours and salary satisfaction); SF 12 Scale; and The Personal Wellbeing Index questionnaire. Two-sample T-Test, exploratory factor analysis and multiple linear regressions were conducted for tracking the differences between participants in homogeneous and heterogeneous programs. Results: A significant difference was found between the programs in two QOL components, insofar as satisfaction with the standard of living, together with health satisfaction were rated higher for participants in the heterogeneous program than for their homogeneous program counterparts. Furthermore, the results indicate that physical health and gender were the most important variables in explaining QOL in both programs, while the employment variables were not significant. Discussion: Since the research findings show that the employment-related-items aren't significant in predicting the employees' QOL, the definition and suitability of extended employment environments as a mental health service must be reexamined. Cultural elements may also have an impact on QOL when the programs are located in a traditional town, with gender playing a key role. The family's role is pivotal in traditional societies, influencing an individual's ability to participate in employment programs and the support they receive. In patriarchal societies, there can be added pressure on men with psychiatric disabilities to conform to societal expectations. Given the general lack of health awareness in Arab communities, there is a need to develop additional projects or incorporate physical health improvement as a rehabilitation goal when working with individuals with psychiatric disabilities, regardless of the type of community rehabilitation program.